Effectiveness of dynamic hedging using options on the WIG20 in current market conditions - Węgrzyn, Ryszard (Skuteczność hedgingu dynamicznego z zastosowaniem opcji na WIG20 w aktualnych warunkach rynkowych, 2020)
Based on previous research on the deviations of the prices of options on the WIG20 from the arbitrage restrictions and features, it was found that the number and scale of these deviations clearly decreased, thus improving the quality of the arbitrage pricing of options. The purpose of this work in this context is to determine the effectiveness of dynamic hedging using options on the WIG20 in current market conditions and to compare the results with the results of previously conducted research. The study was carried out using the historical scenario method based on data from 2017-2018 shared by the Warsaw Stock Exchange. To compare the effectiveness of dynamic hedging, Value at Risk was applied to the unhedged portfolio and portfolios hedged by a specific hedging method. Based on the research, it can be concluded that among the delta, delta-gamma and delta-gamma-vega hedging analyzed, the most effective solution in the current market conditions is delta hedging. The research results indicate that despite qualitative changes on the market that improve the option price relations the delta-gamma and delta-gamma-vega hedging are in practice worse solutions than delta hedging
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 2, s. 109-119
Keywords: option; hedging; delta; gamma; vega; opcja